The Effect of Psychological Capital on Professional Compatibility: Analytical Research in The General Directorate of Administrative Affairs, The Headquarters of The Ministry of Education - Qais Ahmed, Arwa; Mahdi Saleh, Khaled (Journal of Economics and Administrative Sciences, 2025)
This research explores psychological capitals influence on professional compatibility among its employees in the General Directorate for Administrative Affairs, Ministry of Education, Iraq. Psychological states include self-efficacy, optimism, hope, and flexibility, which are essential in preparing employees so they can adjust accordingly to their professional roles. In addition, it will examine professional compatibility through some of its dimensions such as the nature of work, work environment, relationships with colleagues, and relationships with supervisors.The research showed a strong impact of positive psychological characteristics, including a proactive attitude and resilience, in the adaptability of an individual in the diversity of workplace challenges and alignment with the objectives of the organization. Moderate levels of psychological capital among employees with a combination of inadequate managerial support and dissatisfaction with the work environment inhibited the actualization of professional compatibility.Emphasis on the study has been put forward for developing psychological capital through improved managerial practices such as open communication, participatory decision making, and a support-the-work environment. This is very vital for effective improvement in employee integration, satisfaction, and ultimately performance, which is expected to strengthen the overall effectiveness of the organization to accomplish its goals.